2015
DOI: 10.1097/qad.0000000000000953
|View full text |Cite|
|
Sign up to set email alerts
|

The size of the expressed HIV reservoir predicts timing of viral rebound after treatment interruption

Abstract: Objectives Therapies to achieve sustained antiretroviral therapy-free HIV remission will require validation in analytic treatment interruption (ATI) trials. Identifying biomarkers that predict time to viral rebound could accelerate the development of such therapeutics. Design A pooled analysis of participants from 6 AIDS Clinical Trials Group ATI studies to identify predictors of viral rebound. Methods Cell-associated DNA (CA-DNA) and CA-RNA were quantified in pre-ATI PBMC samples, and residual plasma vire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
330
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(344 citation statements)
references
References 45 publications
12
330
0
2
Order By: Relevance
“…circulating resting CD4 + T cells obtained via apheresis. Changes in HIV RNA levels within the resting CD4 + T cell pool are most likely to represent the true reversal of latency and recent upregulation of HIV proviral expression, rather than HIV expression in the "active reservoir" of HIV-RNA-expressing cells found in circulating total CD4 + T cell pools (15). Further, the measurement of resting CD4 + T cell-associated HIV RNA (rca-HIV RNA) in 36 replicate pools of 1 million resting CD4 + T cells ensures a robust and precise assessment of changes in HIV RNA expression (4).…”
Section: Resultsmentioning
confidence: 99%
“…circulating resting CD4 + T cells obtained via apheresis. Changes in HIV RNA levels within the resting CD4 + T cell pool are most likely to represent the true reversal of latency and recent upregulation of HIV proviral expression, rather than HIV expression in the "active reservoir" of HIV-RNA-expressing cells found in circulating total CD4 + T cell pools (15). Further, the measurement of resting CD4 + T cell-associated HIV RNA (rca-HIV RNA) in 36 replicate pools of 1 million resting CD4 + T cells ensures a robust and precise assessment of changes in HIV RNA expression (4).…”
Section: Resultsmentioning
confidence: 99%
“…PK-parameters were estimated by performing a non-compartmental analysis (NCA) using WinNonlin 6.3. Kaplan–Meier survival curves were used to compare time to rebound in trial participants to participants in previous ATI studies conducted by ACTG 29 . To exclude the possibility that the observed delay in rebound is confounded by clinical factors, we compared the clinical variables between the control (ACTG trial participants) and treated group using a two-sided Fisher's Exact test for categorical variables (gender and CD4 Nadir) and an unpaired Wilcoxon test (two-sided) for continuous variables (age, years on ART and CD4 count before ATI initiation) (Supplementary Table 7).…”
Section: Methodsmentioning
confidence: 99%
“…The left y -axis shows plasma viral loads in RNA copies per ml (black curves), and right y -axis shows antibody levels measured by ELISA (red curves). Average rebound time point (2.6 weeks, Supplementary Table 6) in 52 ACTG trial participants who underwent ATI without antibody treatment 29 is shown with dotted lines. Grey areas indicate ART therapy.…”
Section: Figurementioning
confidence: 99%
“…Prior work showed that CA HIV-1 DNA and RNA remain detectable in most chronically infected individuals despite suppressive ART (7,8). Although the association of CA HIV-1 DNA and RNA levels with the size of the latent HIV-1 reservoir has been called into question (9), recent studies suggest that CA HIV-1 DNA and RNA levels may predict the time to virological rebound after ART cessation and thus may serve as clinically relevant biomarkers (10,11).…”
mentioning
confidence: 99%